Identification of Ciwadon Cave as geotourism site using Modified-Geosite Assessment Model (M-GAM) in Jonggol, West Java, Indonesia - Sucahyanto; Ode Sofyan Hardi; Sony Nugratama Hijrawadi; Cayden Nusantoro Liu; Lyzia Nabilla (Geology, Ecology, and Landscapes)
The convergence-subduction process has uplifted the shallow waters in the southern part of Java Island, forming karst morphology with Ciwadon Cave located in Jonggol Subdistrict, West Java, Indonesia. This study aims to evaluate Ciwadon Cave as a geotourism site from the perspectives of visitors and experts, as a basis to enhance its suitability and potential. Modified-Geosite Assessment Model (M-GAM) was used and data were collected from 40 visitors and 6 experts. The assessment results provided a detailed evaluation of the site’s conditions and potential as geotourism destination. Scores for various indicators and sub-indicators were categorized into five grades, ranging from low (0.00) to very high (1.00), culminating in an overall ranking that identified areas of improvement. Ciwadon Cave achieved a main value score of 6.67 and an additional value score of 9.14, placing it in field Z32 were achieved. In this framework, the results were intended to guide improvement in developing Ciwadon Cave into a prominent geotourism site.